GABA Analogues and Related Mono-/Bifunctional Building Blocks Derived from the Fluorocyclobutane Scaffold - Feskov, Illia O.; Golub, Bohdan; Vashchenko, Bohdan V.; Levterov, Vadym V.; Kondratov, Ivan S.; Grygorenko, Oleksandr O.; Haufe, Guenter (European Journal of Organic Chemistry, 2020)
A series of GABA analogs and related mono- and bifunctional building blocks based on the monofluorinated 1,3-disubstituted cyclobutane scaffold was designed and synthesized. The synthetic approaches included desilylative deoxyfluorination of TMS-protected cyanohydrin and iodofluorination of methylenecyclobutane carboxylate as the key steps. Both approaches were highly efficient for the multigram synthesis of gamma- and delta-amino acids, monoprotected diamines, amino alcohols, and hydroxy acids. The first method was diastereoselective (dr3:1) but it failed to produce the target products as pure, separable diastereomers. On the contrary, the second approach lacked diastereoselectivity but provided purecisandtransisomers of the corresponding fluorocyclobutanes by separation of diastereomers; the products were obtained on up to 100 g scale in a single run. Moreover, the method was applied for the preparation of 3-azabicyclo[3.1.1]heptane derivatives. X-ray diffraction studies showed that the synthesized building blocks are appropriate analogs of GABA with either somewhat larger or smaller size as compared to the parent amino acid.
CRIS-Team WoS Importer:2020-08-07